Steroid 5α-reductase 2 deficiency leads to reduced dominance-related and impulse-control behaviors. (May 2018) - Mosher, Laura J.; Godar, Sean C.; Morissette, Marc; McFarlin, Kenneth M.; Scheggi, Simona; Gambarana, Carla; Fowler, Stephen C.; Di Paolo, Thérèse; Bortolato, Marco
Highlights: 5α-reductase 2 (5αR2) catalyzes the conversion of testosterone into DHT. We found that 5αR2 knockout (KO) mice have reduced dominance-related behaviors. These deficits are accompanied by lower novelty-seeking and risk-taking. 5αR2 KO mice exhibit reduced D2 -like receptor binding in the nucleus accumbens. Abstract: The enzyme steroid 5α-reductase 2 (5αR2) catalyzes the conversion of testosterone into the potent androgen 5α-dihydrotestosterone. Previous investigations showed that 5αR2 is expressed in key brain areas for emotional and socio-affective reactivity, yet the role of this enzyme in behavioral regulation remains mostly unknown. Here, we profiled the behavioral characteristics of 5αR2 heterozygous (HZ) and knockout (KO) mice, as compared with their wild-type (WT) littermates. While male 5αR2 KO mice displayed no overt alterations in motoric, sensory, information-processing and anxiety-related behaviors, they exhibited deficits in neurobehavioral correlates of dominance (including aggression against intruders, mating, and tube dominance) as well as novelty-seeking and risk-taking responses. Furthermore, male 5αR2 KO mice exhibited reduced D2 -like dopamine receptor binding in the shell of the nucleus accumbens – a well-recognized molecular signature of social dominance. Collectively, these results suggest that 5αR2 is involved in the establishment of social dominance and its behavioral manifestations. Further studies are warranted to understand how the metabolic actions of 5αR2 on steroid profile may be implicated in social ranking, impulse control, and the modulation of dopamine receptor expression in the nucleus accumbens.